Analisa Perancangan Sistem Informasi Pada Toko Rafatar Berbasis Web Menggunakan PHP MySQL - Pane, Dinda Nurinayah; Masrizal, Masrizal; Harahap, Syaiful Zuhri; Munthe, Ibnu Rasyid (Universitas Labuhanbatu, 2025)
Rafatar stores today still rely on manual sales systems that are prone to human error, inefficient, and make inventory management difficult. This study aims to design and build a website-based sales system to overcome these problems. The system was developed using the PHP programming language and MySQL database to improve operational efficiency, data accuracy, and expand market reach. For inventory management, this study applies the FIFO method (First-In, First-Out) to ensure accurate stock management and minimize the risk of loss. The development of this website is expected to increase the competitiveness of Rafatar stores in a competitive market.